PERBEDAAN KADAR ZAT BESI SERUM BERDASARKAN STATUS KADAR TIMBAL DARAH PADA PEROKOK AKTIF - Wimpy, Wimpy; Dwi Utami, Hesti (Journal of Nursing and Health, 2025)
Exposure to lead (Pb) from cigarette smoke can interfere with iron (Fe) metabolism in the human body. Inhaled lead enters the bloodstream through the lungs and binds to erythrocytes, potentially affecting the absorption and distribution of iron. Active smokers are at risk of accumulating heavy metals such as lead, which over time may disrupt the balance of essential micronutrients, including iron. This study aims to analyze the difference in serum iron levels based on blood lead status among active smokers. This research used an analytical observational approach with a cross-sectional design. A total of 20 active smokers were selected using purposive sampling. Blood lead levels were measured using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES), while serum iron levels were analyzed using the photometric method on a Cobas C111 device. The results showed that 35% of respondents had blood lead levels exceeding the CDC (Centers for Disease Control and Prevention) threshold of >3,5 µg/dL. Additionally, 15% of respondents had serum iron levels below the normal range, and 10% had levels above the normal reference according to the World Health Organization (WHO). The Independent Samples T-Test revealed a p-value of 0,975 (p > 0,05), indicating no significant difference in serum iron levels between groups with normal and elevated blood lead levels. The mean difference in serum iron between groups was only 0,42 µg/dL, with a 95% confidence interval that was wide and included zero.